2003
DOI: 10.2165/00148581-200305080-00005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Two Once Daily Methylphenidate Formulations (Ritalin?? LA???1 and Concerta??) and Placebo in Children with Attention Deficit Hyperactivity Disorder Across the School Day

Abstract: While both Ritalin LA and Concerta were shown to be effective, the different release profiles of each formulation can result in distinct differences between the effects on measures of attention and deportment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 7 publications
5
42
0
1
Order By: Relevance
“…In contrast, children's behavior while on MLR MPH or IR MPH displayed an initial improvement, subsequently remaining constant over time. These results indicate that ADHD symptoms are somewhat mild in the morning and increase in severity throughout the day and confirm previous findings (Pelham et al 2001;Lopez et al 2003). Both MLR MPH and IR MPH prevented this behavioral deterioration but placebo did not.…”
Section: Figsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, children's behavior while on MLR MPH or IR MPH displayed an initial improvement, subsequently remaining constant over time. These results indicate that ADHD symptoms are somewhat mild in the morning and increase in severity throughout the day and confirm previous findings (Pelham et al 2001;Lopez et al 2003). Both MLR MPH and IR MPH prevented this behavioral deterioration but placebo did not.…”
Section: Figsupporting
confidence: 91%
“…The CPT is a widely used cognitive task that measures patient attention and has been shown to be sensitive to MPH treatment effects in children with ADHD (Pelham et al 1987;Pelham et al 1990;Riccio et al 2001). Previous studies have shown improvements in commission and/or omission errors in children with ADHD treated with MPH (Aman et al 1987;Aman et al 1991;Losier et al 1996). In this study following MPH treatment, the number of omission errors dropped significantly compared to placebo, whereas the number of commission errors, or false positives, remained constant.…”
Section: Figmentioning
confidence: 99%
“…23 Ritalin LA ® capsules have also been compared to Concerta ® in a single-blind, placebo-controlled, crossover study. 24 In the study, Ritalin LA 28 Transdermal delivery of methylphenidate provides a treatment option for children who have difficulty swallowing oral medications or if they would benefit from tailoring the duration of effect specifically for their daily needs. 29 The Daytrana ® patch is a multipolymeric adhesive platform that is designed to release methylphenidate consistently upon application to intact skin.…”
mentioning
confidence: 99%
“…Medication for ADHD has traditionally been with indirect dopamine agonists, of which methylphenidate is the most commonly used drug [18,19]. The participants with ADHD tested in the present study were all medicated with methylphenidate.…”
Section: Introductionmentioning
confidence: 99%